ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENINGKATAN PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) - ., Yulizawati (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
BACKGROUND Controlling the population of Indonesia requires the proper use of contraception by couples of childbearing age. Intrauterine device is a long-term contraceptive Alar highly effective, yet very little is used that needs to be analyzed factors that can leverage the increased use of the intrauterine device. OBJECTIVE to analyze factors associated with the increased use of an intrauterine device (IUD). METHODS Data were obtained from 100 respondents and 100 respondents IUD users non IUD users by analyzing the factors of knowledge, attitude, behavior and motivation. Bivariate analysis performed using Mann Whitney test, multivariate analysis using multiple logistic regression. RESULTS multiple logistic regression calculation that the attitude of family planning acceptors related WUS highly significant (p <0.001) for IUD use. While the variables of knowledge, behavior and motivation are not correlated (p = <0.05). CONCLUSIONS Increased use of IUD can be done with emphasis on changing attitudes factor couples of childbearing age. Policy and decision-making and budgeting funds for the IUD should consider factors WUS attitude. Keywords: Knowledge, attitudes, behaviors, motivations, IUD